Design and validation of an entrepreneurial attitude questionnaire in state educational institutions of Metropolitan Lima - Iglesias Landa , Dulce Estefania (2025)
The strengthening of entrepreneurial attitudes is presenting a new challenge in the new current demands and diverse economic problems of our country, because it is part of the disposition of the person to act and seek alternative solutions to various problems in education and for the benefit of society (Díaz, 2011; Fragoso et al., 2021; Zegarra, 2009). However, there are no adequate instruments with psychometric evidence or adapted to our educational context. Therefore, a study was carried out to measure the level of entrepreneurial attitude in 131 teachers from state institutions of UGEL 01 of Metropolitan Lima. This 25-item questionnaire underwent several rigorous validation procedures. In the case of content validation by means of Aiken's V, it showed favorable values for relevance (P= 0.94), clarity of language (CL=0.94) and relevance (R=0.94). For the confirmatory factor analysis, it confirmed adequate adjustment indexes: Xs2/gl=1.426, SRMR=.057, RMSEA=.057, CFI=0.931, TLI=0.924. Finally, in reliability it presented an excellent level (0.96). Therefore, this instrument is valid and useful to know the entrepreneurial attitudes of teachers in an educational institution and to continue strengthening improvements in their training.